SOCIOECONOMIC CONDITIONS AND SUCCESS IN HIGHER EDUCATION: Methodological and analytical issues - Martins, SC; Mauritti, R; Costa, AF (Eurostudent Researchers' Forum, 2017)
One first objective of this presentation proposal refers to the discussion on the possible inclusion of the school or academic success issues - before and during the presence in higher education - and their relationship with the socio-economic conditions of students in higher education in several European countries. Even recognizing that the questionnaire model defined by Eurostudent is already long, we believe that this issue can be absolutely strategic in the context of surveys applied to this population. Thus, Eurostudent could fill a lack of knowledge on academic success of students in higher education. The second part of this presentation concerns the methodological issues and the implementation of surveys related to this subject. This theme has a huge complexity, but it can get even more complex if it is to be in the various national questionnaires, having in view the comparability across countries. In the national survey, in Portugal, we have included a module on success in higher education and in the previous education pathways in Eurostudent III and we are planning to include it again in the next round of Eurostudent (EVI). Some of the results from that study (Portuguese EIII survey), however, are very interesting. For instance, men are more unsuccessful than women, and older students are more likely to fail. Trajectories without retentions occur more in the most disadvantaged social classes and in less educated families. However, the framework and institutional characteristics of educational institutions seem to be the most important when explaining retention in higher education. About 30% of students in tertiary education reported that they had already been held for one year (by poor school results) before entering higher education. We will present the central issues that are included and the new possibilities for analyzes with Eurostudent data taking this dimension into account. Having this debate and the possibilities of these questions included in the next survey model Eurostudent (VII) would be very important and could contribute to a renewed analysis of access and the social dimension in the context of a European area for higher education.